Capacity Decay and Remediation of Nafion‐based All‐Vanadium Redox Flow Batteries. Issue 2 (3rd December 2012) - Luo, Qingtao; Li, Liyu; Wang, Wei; Nie, Zimin; Wei, Xiaoliang; Li, Bin; Chen, Baowei; Yang, Zhenguo; Sprenkle, Vincent
Abstract The relationship between electrochemical performance of vanadium redox flow batteries (VRBs) and electrolyte composition is investigated, and the reasons for capacity decay over charge–discharge cycling are analyzed and discussed herein. The results show that the reasons for capacity fading over real charge–discharge cycling include not only the imbalanced vanadium active species, but also the asymmetrical valence of vanadium ions in positive and negative electrolytes. The asymmetrical valence of vanadium ions leads to a state‐of‐charge (SOC)‐range decrease in positive electrolytes and a SOC‐range increase in negative electrolytes. As a result, the higher SOC range in negative half‐cells further aggravates capacity fading by creating a higher overpotential and possible hydrogen evolution. Based on this finding, we developed two methods for restoring lost capacity, thereby enabling long‐term operation of VRBs to be achieved without the substantial loss of energy resulting from periodic total remixing of electrolytes.